Chemotactic Adaptation Is Altered by Changes in the Carboxy-Terminal Sequence Conserved among the Major Methyl-Accepting Chemoreceptors - Okumura, Hisashi (American Society for Microbiology, 1998)
In Escherichia coli and Salmonella typhimurium, methylation and demethylation of receptors are responsible for chemotactic adaptation and are catalyzed by the methyltransferase CheR and the methylesterase CheB, respectively. Among the chemoreceptors of these species, Tsr, Tar, and Tcp have a well-conserved carboxy-terminal motif (NWET/SF) that is absent in Trg and Tap. When they are expressed as sole chemoreceptors, Tsr, Tar, and Tcp support good adaptation, but Trg and Tap are poorly methylated and supported only weak adaptation. It was recently discovered that CheR binds to the NWETF sequence of Tsr in vitro. To examine the physiological significance of this binding, we characterized mutant receptors in which this pentapeptide sequence was altered. C-terminally-mutated Tar and Tcp expressed in a receptorless E. coli strain mediated responses to aspartate and citrate, respectively, but their adaptation abilities were severely impaired. Their expression levels and attractant-sensing abilities were similar to those of the wild-type receptors, but the methylation levels of the mutant receptors increased only slightly upon addition of attractants. When CheR was overproduced, both the adaptation and methylation profiles of the mutant Tar receptor became comparable to those of wild-type Tar. Furthermore, overproduction of CheR also enhanced adaptive methylation of wild-type Trg, which lacks the NWETF sequence, in the absence of any other chemoreceptor. These results suggest that the pentapeptide sequence facilitates effective adaptation and methylation by recruiting CheR.